Pengaruh Current Ratio (CR) dan Debt To Asset Ratio (DAR) terhadap Return on Asset (ROA) Pada PT Mitra Adiperkasa Tbk Periode 2015-2024 - Rosmalina, Rahmah; Suraya, Amthy (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the effect of Current Ratio (CR) and Debt To Asset Ratio (DAR) on Return On Assets (ROA) at PT Mitra Adiperkasa Tbk for the 2015-2024 period partially or simultaneously. Type of research. The type of research used is quantitative. The sample used in this study is the financial statements in the form of financial position statements and profit and loss statements of PT Mitra Adiperkasa Tbk for the 2015-2024 period. The analysis technique uses descriptive statistical analysis, classical assumption tests, simple linear regression analysis, multiple linear regression analysis, coefficient of determination (Adjusted R2), t test and f test using SPSS Version 27. The results of this study indicate that partially, Current Ratio (CR) does not have a significant effect on Return On Assets (ROA) with the results of the t-value test t table (1.759 2.365) and a significant value greater than 0.05, namely 0.122 (0.122 0.05). Debt To Asset Ratio (DAR) has a significant negative effect on Return On Asset (ROA) with the results of the t-test being greater than the t-table (-4.491 2.365) and a significant value smaller than 0.05, namely 0.003 (0.003 0.05). Simultaneously, there is an influence between the Current Ratio (CR) Debt To Asset Ratio (DAR) on Return On Asset (ROA).